solve the following equation or problem:-
Attachments:
![](https://hi-static.z-dn.net/files/d66/6236f8952da19616f159de073c00da3d.jpg)
Answers
Answered by
0
so simpleee and easy ques ...........
Attachments:
![](https://hi-static.z-dn.net/files/d08/56b0a709481f58c4764cdc673a630d19.jpg)
faltuboy:
plzz aarti if u like answer plzz mark it as brainlist
Answered by
1
Hi there!
Here's the answer:
°•°•°•°•°<><><<><>><><>°•°•°•°•°
49^(3x-1) ÷ 7^(-x) = 7^12
=> 7²^(3x-1) ÷ 7^(-x) = 7^12
°•° (a^m)^n = a^(m×n)
=> 7^[2(3x-1)] ÷ 7^(-x) = 7^12
=> 7^(6x-2) ÷ 7^(-x) = 7^12
°•° a^m ÷ a^n = a^(m-n)
=> 7^[(6x-2)-(-x)] = 7^12
=> 7^[6x-2+x] = 7^12
=> 7^(7x-2) = 7^12
°•° a^m = a^n => m= n
7x-2 = 12 => 7x = 14
•°• x = 2
°•°•°•°•°<><><<><>><><>°•°•°•°•°
©#£€®$
:)
Hope it helps
Here's the answer:
°•°•°•°•°<><><<><>><><>°•°•°•°•°
49^(3x-1) ÷ 7^(-x) = 7^12
=> 7²^(3x-1) ÷ 7^(-x) = 7^12
°•° (a^m)^n = a^(m×n)
=> 7^[2(3x-1)] ÷ 7^(-x) = 7^12
=> 7^(6x-2) ÷ 7^(-x) = 7^12
°•° a^m ÷ a^n = a^(m-n)
=> 7^[(6x-2)-(-x)] = 7^12
=> 7^[6x-2+x] = 7^12
=> 7^(7x-2) = 7^12
°•° a^m = a^n => m= n
7x-2 = 12 => 7x = 14
•°• x = 2
°•°•°•°•°<><><<><>><><>°•°•°•°•°
©#£€®$
:)
Hope it helps
Similar questions